Bioactive caffeic acid derivatives from Wedelia trilobata. (March 2017) - Ren, Hui; Xu, Qiao-Lin; Zhang, Mei; Dong, Li-Mei; Zhang, Qiang; Luo, Bi; Luo, Qin-Wen; Tan, Jian-Wen
Graphical abstract: Highlights: Two new caffeic acid derivatives (1 and2 ) were isolated from Wedelia trilobata . Four known caffeic acid derivatives (3 –6 ) were also obtained and identified. The structures of the isolated compounds were elucidated by spectroscopic means. Compounds1, 2, 4 and5 showed α -glucosidase and/or tyrosinase inhibitory activity. Abstract: Two new caffeic acid derivatives, p -hydroxyphenyl caffeate (1 ) and methyl 3-(7-methoxy-dihydrocaffeoyl)-5-caffeoyl quinate (2 ), were isolated from the whole plant of Wedelia trilobata, along with four known ones, neochlorogenic acid methyl ester (3 ), methyl 4, 5-di- O -caffeoyl quinate (4 ), methyl 3, 5-di- O -caffeoyl quinate (5 ) and chlorogenic acid methyl ester (6 ). Their structures were elucidated on the basis of detailed spectroscopic analysis. They were all isolated from plant W. trilobata for the first time. Compounds1, 2, 4 and5 showed significantly in vitro α -glucosidase inhibitory activity with IC50 values from 0.029 to 0.362 mM, which were more potent than the reference compound acarbose (IC50 0.410 mM). Compound1 was further revealed to show interesting in vitro tyrosinase inhibitory activity (IC50 2.00 μM) much stronger than positive control kojic acid (IC50 12.55 μM).